Between Clicks and Convictions: Youth Political Participation on Facebook in Indonesia and Pakistan - Hussain, Wafa; Gilani, Irum; Shaker, Thanaa (Jurnal Sosiologi Reflektif, 2025)
Social media has emerged as a pivotal arena for youth political participation, particularly within Muslim-majority societies where access to formal civic channels is often constrained. Despite growing interest in digital political engagement, comparative research remains limited in addressing how socio-cultural and political variables mediate online participation. This study investigates how Muslim youth in Indonesia and Pakistan utilize Facebook to articulate political ideologies, engage in civic discourse, and mobilize collective action. Employing a mixed-method approach, the study draws on both quantitative and qualitative data collected through an online survey administered to 30 purposively selected respondents (15 from each country), comprising Master's and PhD students active in digital political discussions. The survey incorporated both closed-ended items and open-ended questions to capture measurable patterns and nuanced perspectives. The researchers applied thematic and descriptive analyses to interpret trends and narratives emerging from the data. The findings reveal contrasting modes of engagement: Indonesian youth predominantly exhibit issue-oriented, personalized political expression, while the Pakistani youth counterparts demonstrate more ideologically aligned, affectively polarized participation linked to partisan narratives. The implication of these findings is that both policy design and theoretical models of youth political participation must account for cultural and structural specificities, as context-sensitive approaches are essential for effectively understanding and fostering civic engagement in diverse Muslim-majority societies. Media sosial telah muncul sebagai arena penting bagi partisipasi politik kaum muda, khususnya di masyarakat mayoritas Muslim, dimana akses terhadap saluran-saluran kewargaan formal seringkali terbatas. Meskipun minat terhadap keterlibatan politik digital terus meningkat, riset komparatif masih terbatas dalam mengkaji bagaimana variabel sosial, kultural, dan politik memediasi partisipasi daring. Penelitian ini menjelaskan bagaimana pemuda Muslim di Indonesia dan Pakistan memanfaatkan Facebook untuk mengartikulasikan ideologi politik, terlibat dalam diskursus kewargaan, dan memobilisasi aksi kolektif. Dengan menggunakan pendekatan mixed-method, melalui survei daring terhadap 30 responden terpilih secara purposif (masing-masing 15 dari Indonesia dan Pakistan), yang terdiri atas mahasiswa magister dan doktoral yang aktif dalam diskusi politik digital. Survei ini mencakup pertanyaan tertutup dan pertanyaan terbuka untuk menangkap pola-pola yang terukur sekaligus perspektif yang lebih mendalam. Analisis tematik dan deskriptif digunakan untuk menafsirkan tren serta narasi dari data yang telah dihimpun. Temuan menunjukkan adanya perbedaan pola partisipasi, yakni: pemuda Indonesia cenderung mengekspresikan politik secara personal dan berbasis isu, sedangkan pemuda Pakistan lebih menunjukkan keterlibatan yang terpolarisasi secara afektif dan berorientasi pada ideologi, yang terkait dengan narasi partisan. Implikasi dari temuan ini adalah bahwa baik dalam perencanaan kebijakan maupun pengembangan teoretis partisipasi politik pemuda harus mempertimbangkan kekhasan budaya dan struktur sosial, sebab hal ini sangat penting untuk memahami dan mendorong keterlibatan kewargaan di masyarakat dengan penduduk mayoritas Muslim.